Training quantification and periodization during live high train high at 2100 m in elite runners: An observational cohort case study - Sharma, A. P.; Saunders, P. U.; Garvican-Lewis, L. A.; Périard, J. D.; Clark, B.; Gore, C. J.; Raysmith, B. P.; Stanley, J.; Robertson, E. Y.; Thompson, K. G. (Journal of Sports Science & Medicine, 2018)
The questionable efficacy of Live High Train High altitude training (LHTH) is compounded by minimal training quantification in many studies. We sought to quantify the training load (TL) periodization in a cohort of elite runners completing LHTH immediately prior to competition. Eight elite runners (6 males, 2 females) with a VO2peak of 70 ± 4 mL·kg-1·min-1 were monitored during 4 weeks of sea-level training, then 3-4 weeks LHTH in preparation for sea-level races following descent to sea-level. TL was calculated using the session rating of perceived exertion (sRPE) method, whereby duration of each training session was multiplied by its sRPE, then summated to give weekly TL. Performance was assessed in competition at sea-level before, and within 8 days of completing LHTH, with runners competing in 800 m (n = 1, 1500 m/mile (n = 6) and half-marathon (n = 1). Haemoglobin mass (Hbmass) via CO rebreathing and running economy (RE) were assessed pre and post LHTH. Weekly TL during the first 2 weeks at altitude increased by 75% from preceding sea-level training (p = 0.0004, d = 1.65). During the final week at altitude, TL was reduced by 43% compared to the previous weeks (p = 0.002; d = 1.85). The ratio of weekly TL to weekly training volume increased by 17% at altitude (p = 0.009; d = 0.91) compared to prior sea-level training. Hbmass increased by 5% from pre- to post-LHTH (p = 0.006, d = 0.20). Seven athletes achieved lifetime personal best performances within 8 days post-altitude (overall improvement 1.1 ± 0.7%, p = 0.2, d = 0.05). Specific periodization of training, including large increases in training load upon arrival to altitude (due to increased training volume and greater stress of training in hypoxia) and tapering, were observed during LHTH in elite runners prior to personal best performances. Periodization should be individualized and align with timing of competition post-altitude.